AN OVERVIEW ON ORAL MUCOCELE - Vijaya Kumaran, Ghayathri; Jagannathan, Nithya (International Journal of Psychosocial Rehabilitation, 2020)
Mucocele is a common lesion of the oral mucosa that results from an alteration of minor salivary glands due to mucous accumulation. The most frequent localizations of these lesions are the lower lip mucosa. It also presents in other locations like the tongue, buccal mucosa, soft palate, retromolar pad, and lower labial mucosa. Two histological types exist: extravasation and retention. Mucoceles can appear at any site of the oral mucosa where minor salivary glands are present. Mucoceles can affect the general population, but most commonly young patients between the ages of 20 and 30 years. Clinically, they consist of soft bluish and transparent cystic swelling, which occurs spontaneously.